Similar 5-Year Survival in Transfemoral and Transapical TAVI Patients: A Single-Center Experience - Mork, Constantin; Twerenbold, Raphael; Gahl, Brigitta; Eckstein, Friedrich; Jeger, Raban; Kaiser, Christoph; Reuthebuch, Oliver (Bioengineering (Basel), 2023)
Transapical transcatheter aortic valve implantation (TA-TAVI) is generally considered to be associated with increased morbidity and mortality compared with transfemoral transcatheter aortic valve implantation TAVI (TF-TAVI). We aimed to compare different patient risk profiles, access-related complications, and long-term survival using inverse probability treatment weighting. This is a retrospective, single-center analysis of 925 consecutive patients with aortic valve stenosis undergoing TF-TAVI (n = 802) or TA-TAVI (n = 123) at the University Hospital Basel, Switzerland, as a single procedure between September 2011 and August 2020. Baseline characteristics revealed a higher perioperative risk as reflected in the EuroSCORE II (geometric mean 2.3 (95% confidence interval (CI) 2.2 to 2.4) vs. 3.7 (CI 3.1 to 4.5); before inverse probability of treatment weighting (IPTW) p < 0.001) in the transfemoral than in the transapical group, respectively. After 30 days, TF-TAVI patients had a higher incidence of any bleeding than TA-TAVI patients (TF-TAVI n = 146 vs. TA-TAVI n = 15; weighted hazard ratio (HR) 0.52 (0.29 to 0.95); p = 0.032). After 5 years, all-cause mortality did not differ between the two groups (TF-TAVI n = 162 vs. TA-TAVI n = 45; weighted HR 1.31, (0.92 to 1.88); p = 0.138). With regard to our data, we could demonstrate, despite a higher perioperative risk, the short- and long-term safety and efficacy of the transapical approach for TAVI therapies. Though at higher perioperative risk, transapically treated patients suffered from less bleeding or vascular complications than transfemorally treated patients. It is of utmost interest that 5-year mortality did not differ between the groups.